Comparison of Endovenous Laser and Radiofrequency Ablation in Treating Varices in the Same Patient - Bozoglan, Orhan; Mese, Bulent; Eroglu, Erdinc; Ekerbiçer, Hasan Cetin; Yasim, Alptekin (Journal of Lasers in Medical Sciences, 2017)
Introduction: To compare endovenous laser ablation (EVLA) and radiofrequency ablation (RFA) in different legs in the same individual in patients with venous insufficiency. Methods: Sixty patients with bilateral saphenous vein insufficiency were included. EVLA or RFA was applied to one of the patient’s legs and RFA or EVLA to the other leg. Results: EVLA and RFA complications were hyperemia at 20.7% and 31.0%, ecchymosis at 31.0% and 51.7% and edema at 27.6% and 65.5%, respectively. The rate of recanalization was 6.8% in the RFA group. No recanalization was observed in EVLA group. The level of patients satisfied with EVLA was 51.7%, compared to 31.0% for RFA, while 17.2% of patients were satisfied with both procedures. Times to return to daily activity were 0.9 days in the EVLA group and 1.3 days in the RFA group. Conclusion: EVLA procedure may be superior to RFA in certain respects.